2D/2d mt/m-cn composite with enriched interface charge transfer for boosting photocatalytic co2 hydrogenation by h2 to ch4 under visible light - Tahir, B. (Elsevier B. V., 2020)
Well-designed montmorillonite (Mt) coupled graphitic carbon nitride (m-CN) composite for stimulating photocatalytic CO2 hydrogenation with H2 and H2O reducing agents has been investigated. 2D Mt nanosheets were uniformly anchored with 2D m-CN nanosheets for improving charge carrier separation. The photoactivity of 2D/2D Mt/m-CN was tested for CO2 photoreduction with H2O/H2 to CO/CH4 through RWGS and CO2 methanation reactions under visible light. Using 20% Mt/m-CN, highest CO and CH4 yield rate of 253 and 165 μmol g-cat−1h−1 were obtained, 5.9 and 6.4 times high than g-C3N4, respectively. This improved activity reflects synergistic effect between Mt and m-CN, which promotes photo-induced charge carrier separation. More interestingly, during CO2 reduction with hydrogen, CH4 was the main product and its production was 2.1 folds higher than using CO2 reduction by H2O. This selective CO2 hydrogenation to methane was obviously due to single-step CO2 methanation process with proficient H2 oxidation over highly efficient Mt/m-CN composite. The QY for CH4 production of 4.55% was obtained with high stability in cycles over the composite catalyst. The findings from this research would be fruitful for further investigation in CO2 conversion for selective fuels production to provide clean energy.